Time-Varying Skewness in Stock Returns: An Information-Based Explanation - Lakshman, Alles (University of Nebraska - Lincoln, 2004)
There is evidence of regularities in the skewness of asset returns reported in the literature. The literature, however, offers no adequate explanations for these phenomena. Based on a simulation approach, we provide evidence that at least some aspects of skewness can be explained in terms of extant information-based theories in finance. Using a well-accepted model for generating asset returns, we demonstrate that when the effects of the uncertain information hypothesis and Kahneman and Tversky's prospect theory are incorporated in the return-generating process, the resulting return distributions can show negative skewness and variations of skewness with changing economic climates similar to what has been observed in empirical distributions.